0Application Study on Treatment Technology of Geological Disasters Caused by Water and Mud Inrush in Ningchan Tunnel. Issue 1 (October 2020) - Zhang, Danfeng; Xiao, Shilai; Cheng, Liang
Abstract: In the process of tunnel construction, water and mud inrush are engineering disasters which are extremely difficult to deal with and have great harm. With Ningchan Tunnel as the background, and combined with the actual situation of the project site, the causes of water and mud inrush in tunnels with weak geological structure are analyzed. Through safety risk analysis, a comprehensive treatment scheme of "advance pipe-shed reinforcement and curtain grouting" is put forward. By selecting the accumulated vault settlement and accumulated peripheral convergence of 4 typical monitoring sections before and after treatment, the deformation laws of Ningchan Tunnel before and after treatment are summarized: The accumulated vault settlement and accumulated peripheral displacement convergence of the monitoring section after treatment is far less than those before treatment. It shows that reasonable grouting reinforcement, advance pipe-shed reinforcement and other methods are suitable for the treatment of sections with water and mud inrush, and the treatment effect is obvious. It has certain guiding significance for similar tunnel projects.